NOVOS SABERES, NOVAS PERSPECTIVAS: 10 ANOS DO CURSO DE DOUTORADO EM ENFERMAGEM NA UFBA - Coelho, Edméia Almeida Cardoso; Nascimento, Enilda Rosendo do; Paiva, Mirian Santos (Revista Baiana de Enfermagem‏, 2016)
Editorial